An observational study of the relationship between Capacity for Care as an animal shelter management model and cat health, adoption and death in three animal shelters. (September 2017) - Karsten, C.L.; Wagner, D.C.; Kass, P.H.; Hurley, K.F.
Highlights: The impact of implementing a specific shelter management model, Capacity for Care (C4C), at three shelters was reviewed. All shelters showed a higher probability of adoption and lower probability of death (euthanasia/died) for shelter cats after implementation. Cage housing was improved to provide cats more space. All shelters experienced a reduction in total number of housing units. In-shelter cat population decreased due to reductions in housing capacity and implementation of the management model. Isolation populations decreased after shelter management model implementation. Abstract: Animal shelters struggle to function at their 'right size' in terms of physical, staffing and outcome capacity, especially with seasonal fluctuations in cat intake. To address this, a Capacity for Care (C4C) management model was devised to balance health and welfare requirements of all animals while maintaining or improving goals for positive outcomes, such as adoption or transfer. In this observational study of three shelters, applying the C4C management system gave each organization an optimal average daily shelter cat population target (to be achieved through proactive length of stay management) and helped each shelter to increase the size of their feline housing units. Pre- and post-C4C implementation data were evaluated to determine impact on average monthly isolation ward populations and cat outcomes such as adoptions and shelter deaths (euthanasia/died). Improved outcomes including increased adoption probability, decreased shelter death probability and fewer cats requiring infectious disease isolation were seen after C4C institution. Results suggest that implementation of this management model could help other shelters achieve similar results.